Interpretasi Instrumentasi Piezometer Dalam Rangka Pemantauan Keamanan Bendungan Kedung Ombo: Piezometer Instrumentation Interpretation to monitor Kedung Ombo Dam Safety - Gerald Guntur Pandapotan Siregar; fajar aldoko Kurniawan (Siklus : Jurnal Teknik Sipil, 2021)
The embankment dam is the most widely built dam in the world, especially in Indonesia. However, embankment dams are also prone to collapse. Dam failures due to the piping process through the dam body account for 30.5% of the total dam collapses worldwide. Therefore, it is necessary to periodically monitor and evaluate the condition of pore water pressure and seepage in a dam which is usually carried out using installed instrumentation. Very little has been done on instrumentation interpretation of earthfill dams in Indonesia, which is a very worrying condition. It is possible that old or even new dams have shown behavior that leads to a decrease in safety. This condition can be monitored by instrumentation in the dam if interpreted properly. Kedung Ombo Dam as an old embankment dam but has a fairly complete instrumentation can be evaluated for safety related to pore water pressure and phreatic line (seepage line). Pore water pressure evaluation is carried out by collecting piezometer readings and reservoir water level fluctuations over a period of several years. The results of the research on the interpretation of piezometer readings indicate that the overall safety of the Kedung Ombo dam is still good in terms of pore water pressure conditions. However, there are some anomalous conditions that should be investigated further